Design of RoF-VLC Based DWDM Communication System - Vaides, M.; Nawawi, N. M.; Anuar, M.S.; M. N., Junita; Mohd Noor, Muhammad Yusof; Md Zain, Aini Syuhada; Adam, I.; Ramli, Nuraminah; Abdalmunam, Aymen (International Journal of Integrated Engineering, 2025)
Radio over Fiber with Visible Light Communication system (RoF-VLC) is a promising technology that integrates the benefits of optical fiber communication and wireless transmission. This abstract presents a novel approach to enhance the RoF system by integrating VLC with millimeter-wave (mm Wave) technology, leveraging the advantages of both systems. The proposed system utilizes mmWave signals over a single optical fiber link through a Wavelength Division Multiplexing (WDM) technology to enable the simultaneous transmission of multiple VLC system. On the other hand, mm Wave technology leverages the abundant bandwidth available in the millimeter-wave frequency range, enabling high-capacity wireless communication. By combining these technologies, the proposed system achieves high-speed data transmission and increased network capacity. WDM technology plays a crucial role in the proposed system by enabling the simultaneous transmission of VLC and mm Wave signals over a single optical fiber. The RoF-VLC system based on WDM technology is built and simulated using OptiSystem software, with four WDM channels at 450 nm, 450.8 nm, 451.6 nm, and 452.4 nm as an optical source of VLC system and a photodetector as a receiver. Each channel with a 40 GHz radio signal is transmitted over a 40 km of fiber link and a 3 m of VLC channel. This proposed design of RoF-VLC system based on WDM has been analyzed based on the effect of propagation distance (km), modulation format, data rate, and input power. The performance analysis show that this system is achieved by using the values of BER at 2.6355e-009 for channel 1, 7.54389e-010 for channel 2, 5.39904e-010 for channel 3, and 2.45532e-010 for channel 4.